Performance of the three reductions, three gains program in the context of sustainable agricultural development in Vietnam - Tran Che Linh; Thapa, Gopal B.; Soparth Pongquan; Shivakoti, Ganesh P.; International Fellowships Program; Ford Foundation, USA; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2011)
The 2Three Reductions, Three Gains3 (3R3G) program has been implemented in Vietnam since 2001 with the aim of improving farmers{u2019} income and health condition, and soil quality by motivating them to reduce the amounts of seed, fertilizer and pesticide used. This study was carried out to evauate the performance of the program in terms of these stipulated reductions and gains. Primary information was collected through a survey of 9 2 farm households in Binh Long and My D uc communes of Chau Phu district of An Giang province, group discussion, unstructured personal interviews, and case study. The findings of the study revealed a considerable reduction in the amounts of seed and fertilizer, and the frequency pesticide appl ication after farmers{u2019} participation in the 3R3G Porgram. However, the reduction was still below the maximum limit recommended by the An Giang Sub - Department of Plant Protection. The amounts of seed and fertilizer applied varied from one farm household to another. The result of the regression analysis carried out to find out factors influencing the application of seed found farmers{u2019} duration of experience in Chau Phu District, application of seed certified and treated seeds as significantly influencing factors. In regard to the amount of fertilizer applied, soil quality and farmers{u2019} adherence to the fertilizer application guideline made by the An Giang Sub - Department of Plant Protection were the significant determinants. Regarding the frequency of pesticide s sprayed, the amount seed sown, the use of certified and well treated seeds were the significant determiantns. As a result of the reductions in the amounts of seed and fertilizer, and the frequency of pesticide application the quality of soil had improved, eventually increased production of and income from rice cultivation. The comparision of farmers{u2019} health condition before and after participation in the program reveled that it improved considerably due primarily to reduced frequency of pesticide application. Conclusions are drawn and suggestions have been made for improvement of the program effectiveness in the future based on the findings of the study
A thesis submitted in partial fulfillment of requirements for the degree of Master of Science in Regional and Rural Development Planning
Thesis (M. Sc.) - Asian Institute of Technology, 2011
Keywords: Sustainable agriculture -- Vietnam